Growth and Yield Performances of Tubigan Rice Varieties under Abra, Philippines Conditions - Edwin, Milandro (JPAIR Multidisciplinary Research, 2015)
Increased rice production through the use of high yielding varieties is a possible solution for rice shortage in the Philippines. The study on six (6) Tubigan rice varieties which was conducted for wet and dry growing seasons at Abra State Institute of Sciences and Technology, Lagangilang, Abra, Philippines was aimed to determine their growth and yield performances of Tubigan rice varieties under Abra Conditions. Results revealed that there were significant differences in the number of days to mature, height of plants at maturity, number of unfilled grains per panicle, length of panicle, harvest index, weight of 1000 seeds and yield per hectare between the Tubigan varieties. The varieties tested showed highly significant differences in the parameters studied except in the number of filled grains. NSIC Rc 158 outranked the other varieties in yield probably because it produced the highest number of tillers per hill, filled grains per panicle, high harvest index and yield per hectare of 6.4 tons/ha. NSIC Rc160 was the tallest at maturity and produced the longest panicle. NSIC Rc156 produced the highest number of unfilled grains. The yield of all the varieties exceeded the average production of lowland rice in Abra, which was 3.48 t/ha (PhilRice & BAS, 2002). NSIC Rc158 could be grown by rice farmers in irrigated lowland condition in Abra because it exceeded the average yield of the check variety NSIC Rc160 and found acceptable to consumers.